Advance path loss model for LoRaWAN coverage estimation - Van Lic Tran; Tran Dang Khoa Phan; Tran Thi Minh Hanh; Vu Van Thanh; Thai Van Tien; Thai Vu Hien; Tran Anh Kiet (Tạp chí Khoa học và Công nghệ)
This paper demonstrates that, using multiple data points around each gateway allows for the creation of accurate coverage heat maps by using a proposed LoRaWAN coverage estimation algorithm. This method effectively identifies areas with varying signal strength across Da Nang City, highlighting where additional gateways are needed to improve network reliability. Unlike previous studies, this research considers environmental factors such as topography and urban structures, enhancing prediction accuracy. This technique would be essential for optimizing essential for optimizing LPWAN deployments and ensuring efficient resource utilization. Future efforts will focus on refining neural network models and integrating real-time data to support scalable Smart City solutions and a more robust connectivity infrastructure, with this work planned for future research.